2021
DOI: 10.1089/hs.2021.0042
|View full text |Cite
|
Sign up to set email alerts
|

E-Mentoring Female Underrepresented Public Health Student Researchers: Supporting a More Diverse Postpandemic Workforce

Abstract: Within higher education, underrepresented students continue to face inequalities and discrimination, with unique challenges surfacing during the COVID-19 pandemic. Mentoring through formal or informal channels is one way to offer assistance to such students. During COVID-19 lockdowns, as classes and work moved online, mentoring also transitioned online. Electronic mentoring, or e-mentoring, was implemented formally by some universities and informally by independent researchers. This article describes the infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Mentoring, mentoring circles, e-mentoring and one-to-one support programmes are recommended as approaches that can boost the prospects of underrepresented groups in academia generally (Mahayosnand et al, 2021;Sanderson and Spacey, 2021) as well as in biomedical research, healthcare research and academic medical contexts (Athanasiou et al, 2016;Lewis et al, 2016;Valantine et al, 2016). It is suggested that, without such programmes, women and individuals from minority ethnic backgrounds may not be able to access suitable mentors.…”
Section: Mentoring and Mentorshipmentioning
confidence: 99%
“…Mentoring, mentoring circles, e-mentoring and one-to-one support programmes are recommended as approaches that can boost the prospects of underrepresented groups in academia generally (Mahayosnand et al, 2021;Sanderson and Spacey, 2021) as well as in biomedical research, healthcare research and academic medical contexts (Athanasiou et al, 2016;Lewis et al, 2016;Valantine et al, 2016). It is suggested that, without such programmes, women and individuals from minority ethnic backgrounds may not be able to access suitable mentors.…”
Section: Mentoring and Mentorshipmentioning
confidence: 99%
“…Selain itu, kemudahan yang diberikan dari pertemuan daring menjadi pertimbangan bagi mahasiswa sehingga merasa lebih mudah dan juga akan lebih nyaman. Hal ini juga didukung oleh penelitian Ponn et al, 15 setuju bahwa mentoring yang diadakan secara daring memudahkan dalam pelaksanaannya dikarenakan peserta mentoring tidak terbatas oleh jarak lokasi. 15 Namun, terdapat kekurangannya yaitu koneksi internet yang kurang stabil dan mungkin terdapat perbedaan zona waktu antar mahasiswa.…”
Section: Jumlah Mahasiswa Yang Mengikuti Program "Meniscus"unclassified
“…Hal ini juga didukung oleh penelitian Ponn et al, 15 setuju bahwa mentoring yang diadakan secara daring memudahkan dalam pelaksanaannya dikarenakan peserta mentoring tidak terbatas oleh jarak lokasi. 15 Namun, terdapat kekurangannya yaitu koneksi internet yang kurang stabil dan mungkin terdapat perbedaan zona waktu antar mahasiswa. Oleh karena itu, dapat disarankan untuk memilih tempat pertemuan yang tepat baik secara daring dan luring sehingga efektivitas dari program "MENISCUS" dapat tercapai.…”
Section: Jumlah Mahasiswa Yang Mengikuti Program "Meniscus"unclassified
“…Because of the pandemic, SCOPE was hosted virtually for the first time. Research supports the efficacy of virtual mentoring (Mahayosnand, 2000; Mahayosnand et al, 2021), and there were multiple benefits of hosting SCOPE in a virtual format. Specifically, the virtual compared to the in-person format allowed for a more precise mentor–mentee interest match as we were not limited by geographical barriers, decreased the burden of having to travel to attend a mentorship workshop, and increased program access to faculty, graduate, and undergraduate students from different universities across the United States.…”
mentioning
confidence: 93%